Contribution of health and wellness tourism to happiness and quality of life: a comparative study between Portugal and Hungary - Quintela, Joana Alegria Ferreira da Silva (2021)
Since its origin, health and wellness tourism has been related to the history of Portugal and Hungary, currently appearing as an undeniably strategic product for the development of tourism in both countries. The importance of this type of tourism is due to a set of circumstances imposed by contemporary life. Stress levels and working hours, as well as an increase in average life expectancy are some of the factors that converge to a greater concern with well-being issues, aided by an incessant search for happiness and for higher levels of quality of life. In this sense, health and wellness activities, promoted by the Thermal Baths and Spas, figures as means capable of meeting these current needs. The main objective of this thesis is to analyse the contribution of health and wellness tourism to the happiness and quality of life of thermal spas goers, based on a comparative study between Portugal and Hungary. The development of this thesis started from a theoretical basis, grounded on a review of the broad literature on the constructs under analysis, which contributed to the understanding of the use of the concepts of happiness and quality of life in the tourist context. This theoretical approach leveraged the construction of an investigation model and the definition of a set of hypotheses, tested through the results obtained from the empirical part developed throughout the study. The analysis was focused on the demand side, including health and wellness users and tourists in both countries, characterizing them in sociodemographic terms, observing their travel behaviour, assessing their satisfaction with the health and wellness experience, regarding the levels of happiness and quality of life obtained. This analysis is based on an empirical study developed over nine months, whose data were collected in a total of twelve Thermal Baths and Spas, six of them located in the Northern and Central regions of Portugal, and the other six located in the city of Budapest, in Hungary, providing a total of 753 valid responses. In the empirical study, a quantitative approach is made, using descriptive and multivariate statistical analysis, comparing the results obtained in both countries. This analysis allowed to demonstrate the potential of health and wellness tourism on the contribution to the happiness and quality of life of users, according to their different profiles. The main conclusions of the study allow to present a set of theoretical and practical implications for the development of health and wellness tourism in both countries, in a perspective of marketing, complemented with a set of proposals for future research in this area.